Self-Acceptance of The Main Character in Turning Red Movie: A Self-Acceptance Theory Approach - Rohmawati, Zakiyah (University of Surakarta, 2025)
This study explores the process of self-acceptance in the 2022 film Turning Red by examining the journey of the protagonist, Mei Lee, a Chinese-Canadian adolescent navigating puberty, cultural expectations, and familial pressures. Employing a qualitative content analysis approach grounded in self-acceptance theory, the research examines pivotal scenes, dialogues, and symbolic elements to analyse Mei's psychological and emotional development. The analysis of the text reveals several key findings. First, the transformation of Mei into a red panda functions as a metaphor for the chaos of adolescence. Second, this transformation reflects her struggle to reconcile her identity with her mother's rigid cultural expectations. The analysis underscores the role of peer support, rebellious acts, and intergenerational conflict in shaping her journey toward self-acceptance. The study emphasizes the significance of supportive relationships and personal agency in overcoming societal pressures, particularly within the context of immigrant family dynamics. By portraying the red panda as both a literal and symbolic representation of emotional turmoil, the film illustrates universal adolescent challenges while addressing culturally specific narratives. This research contributes to broader discussions on adolescent psychology, multicultural identity, and the role of the media in portraying self-acceptance, offering insights into the intersection of cultural norms and personal growth.